نماذج من الـعمارة الـدينيـة بقصري تقرت وتماسين - بن صغير حضري, يمينة (جامعة الوادي - University of Eloued, 2020)
اهتم الإنسان مند القديم بعمارته الدينية لما للجانب الروحي من اثر فعال في قيام الحضارات سواء كانت ديانات سماوية أو معتقدات وضعية، وذلك باختيار أحسن المواقع، وأصلب مواد للبناء و أجودها، لهذا بقيت هذه المعالم ثابتة لعدة قرون، بالرغم مما قد تتعرض له المباني المدنية من تدهور و انهيار، وعليه فان الزائر لقصور الجنوب الجزائري يلاحظ صمود عمارتها الدينية، وتميز جوامعها ومساجدها عن غيرها من المباني المدنية، حيث بقيت قائمة بالرغم من مرور ألاف السنين، و تعرضها للعديد من العوامل الطبيعية، فبنيت جوامع و مساجد كل من قصري تقرث و تماسين بدورها بكثير من الإتقان و التفنن، مما ساعد على استمرارها و بقائها. Abstract: Since the old time human being had focused on the religious architecture due to the spiritual effect on the establishing civilization on either monotheism or positive religious, by selecting strategic sites on which the edifice is being built with high quality and strong materials, this explain the long life of those monument which last for ages, despite that some of them has been ruined and the collapsed. the visitor of the Ksour in the south of Algeria notice the resistance of the religious architecture of mosques and worship building which still exist even though thousands of years has gone by, and the affect of different natural factors , moreover the visitor attention is drawn by the workmanship and art proficiency by which Mosques and worship edifice in Tamacine and Touggour Ksars has been built, that make them last longer.
مقال
Keywords: عمارة دينية؛ قصر؛ تقرث ؛ تماسين ؛ مسجد; Religious Edifice; Ksar; Touggourt; Tamacine; mosques